Current practice of outpatient rehabilitation services in patients with mobility-impaired paralysis due to stroke or spinal cord injury: a qualitative interview study in Germany - Schmittus, Tiziana; Spingler, Tamara; Hug, Andreas; Weidner, Norbert; Wensing, Michel; Ullrich, Charlotte (Disability and rehabilitation, 2023)
Professionals need to be trained in setting rehabilitation goals and treatments. The continuing education should be based on current evidence and address interprofessionalism. Academization and continuing education in scientific work for therapists should be advanced.Professionals should educate patients about rehabilitation goals and set rehabilitation goals together, both interprofessional coordinated and with the patient (shared decision-making). Activity and participation should be the central aspects. Rehabilitation clinicians should give instructions to therapists on what to do if rehabilitation goals are not worked on.Rehabilitation clinicians should encourage interprofessional collaboration and information exchange where this is not the case. The exchange of information between outpatient professionals should be promoted through appropriate measures, that is, interprofessional meetings could be introduced.The outpatient service catalogue should be revised regarding evidence-based and participation-oriented treatments and enable appropriate cost coverage.
Gesehen am 20.10.2023